Strategi Pemasaran Loyalitas Merek di Media Sosial: Membangun Keterlibatan Pelanggan yang Berkelanjutan - Muhamad Khairullah Jalal; Nina Nurhasanah (BADAN PENERBIT STIEPARI PRESS, 2026)
This study aims to analyze the influence of Social Media Marketing and Customer Engagement on Brand Loyalty, with the Intention to Continue Utilizing as a mediating variable, among active TikTok users who have interacted with Rucas brand content. This study employs a quantitative approach using a survey method with 120 respondents selected through purposive sampling, with criteria of being aged 18–35 years and actively using TikTok. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results indicate that Social Media Marketing and Customer Engagement have a significant positive influence on the Intention to Continue Using. Customer Engagement was also found to have a direct effect on Brand Loyalty, while the direct effect of Social Media Marketing on Brand Loyalty was not significant. Furthermore, the intention to continue using was found to mediate the relationship between social media marketing and customer engagement on brand loyalty. These findings emphasize the importance of building a sustainable experience through social media that is not only attractive but also capable of creating engagement and long-term intentions to lead to strong brand loyalty.